Anterolateral Acromioplasty Reduces Gliding Resistance Between the Supraspinatus Tendon and the Coracoacromial Arch in a Cadaveric Model - Lukas Ernstbrunner, M.D., Ph.D; Jean-David Werthel, M.D., Ph.D; Tobias Götschi, M.E; Alex W. Hooke, M.A; Chunfeng Zhao, M.D (Elsevier, 2024)
Purpose: To investigate the gliding resistance dynamics between the supraspinatus (SSP) tendon and the coracoacromial arch, both before and after subacromial decompression (anterolateral acromioplasty) and acromion resection (acromionectomy). Methods: Using 4 fresh-frozen cadaveric shoulders, acromion shapes were classified (2 type I and 2 type III according to Bigliani). Subacromial bursa and coracoacromial ligament maintenance replicated physiologic sliding conditions. Gliding resistance was measured during glenohumeral abduction (0° to 60°) in internal rotation (IR) and external rotation (ER). Peak gliding resistance between the SSP tendon and the coracoacromial arch was determined and compared between intact, anterolateral acromioplasty, and acromionectomy. Results: Peak SSP gliding resistance during abduction in an intact shoulder was significantly higher in IR than in ER (4.1 vs 2.1 N, P < .001). The mean peak SSP gliding resistance during 0° to 60° glenohumeral abduction in IR in the intact condition was significantly higher compared with the subacromial decompression condition (4.1 vs 2.8 N, P = .021) and with the acromionectomy condition (4.1 vs 0.9 N, P < .001). During 0° to 60° glenohumeral abduction in ER, mean peak SSP gliding resistance in the intact condition was not significantly different compared with the subacromial decompression condition (2.1 vs 2.0 N, P = .999). The 2 specimens with a hooked (i.e. type III) acromion showed significantly higher mean peak SSP gliding resistance during glenohumeral abduction in IR and ER when compared with the 2 specimens with a flat (i.e. type I) acromion (IR: 5.8 vs 3.0 N, P = .006; ER: 2.8 vs 1.4 N, P = .001). Conclusions: In this cadaveric study, peak gliding resistance between the SSP tendon and the coracoacromial arch during combined abduction and IR was significantly reduced after anterolateral acromioplasty and was significantly higher in specimens with a hooked acromion. Clinical Relevance: The clinical benefit of subacromial decompression remains unclear. This study suggests that anterolateral acromioplasty might reduce supraspinatus gliding resistance in those with a hooked acromion and in the typical "impingement" position.